Constructivism Approach in Madrasah Ibtidaiyah Learning - Shulhan, Shulhan (Maharot : Journal of Islamic Education, 2023)
This articleÂ reviews the value of using constructivist teaching strategies in Islamic primary schools. The text was used as a research source for the goals mentioned above, and qualitative methodologies from a library research perspective were applied. The research stages involved topic selection, information exploration, focus determination, data collection, source gathering, preparation of presentations, and compilation of research reports. Content analysis was used for the data analysis. The findings are as follows: First, constructivism is a branch of educational psychology blending cognitivism theory, which holds that the mind is the most crucial aspect of human existence, with behavioristic theory looking at people as blank pieces of paper that teachers may scribe to. As a working hypothesis, every teacher must already have the basic knowledge to teach constructivism. Second, teachers must be adept at presenting learning contexts through various tactics. The learning process was conducted by attending to students' demands. However, as it does not allow trial and error, it is inappropriate for writing involving doctrines. Every instructor must be able to analyze, review, and recreate the concepts created by students. The spiritual dimension, manifested in acts and attitudes, supports teachers' teaching abilities and scientific knowledge.